2017
DOI: 10.1007/s00380-017-1055-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma l-arginine levels distinguish pulmonary arterial hypertension from left ventricular systolic dysfunction

Abstract: Pulmonary arterial hypertension (PAH) is a life-threatening condition, characterized by an imbalance of vasoactive substances and remodeling of pulmonary vasculature. Nitric oxide, formed from l-arginine, is essential for homeostasis and smooth muscle cell relaxation in PAH. Our aim was to compare plasma concentrations of l-arginine, asymmetric dimethylarginine (ADMA), and symmetric dimethylarginine (SDMA) in PAH compared to left ventricular systolic dysfunction (LVSD) and healthy subjects. This was an observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The coincidence of CKD and pulmonary hypertension is associated with a significant increase in patient mortality; therefore, it is important to understand the pathological mechanisms underlying pulmonary hypertension. However, currently, there are many hypotheses [57][58][59][60][61], including a chronic volume overload, which can accelerate pulmonary vascular remodeling. The role of nitric oxide was also suggested because nitric oxide regulates pulmonary vascular tone, and it is a frequent target of pharmacotherapy for pulmonary arterial hypertension.…”
Section: Pulmonary Hypertension In Patients With Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…The coincidence of CKD and pulmonary hypertension is associated with a significant increase in patient mortality; therefore, it is important to understand the pathological mechanisms underlying pulmonary hypertension. However, currently, there are many hypotheses [57][58][59][60][61], including a chronic volume overload, which can accelerate pulmonary vascular remodeling. The role of nitric oxide was also suggested because nitric oxide regulates pulmonary vascular tone, and it is a frequent target of pharmacotherapy for pulmonary arterial hypertension.…”
Section: Pulmonary Hypertension In Patients With Ckdmentioning
confidence: 99%
“…In addition, progressive renal dysfunction and dialysis therapy promote the activation of the inflammatory system. In this context, researchers have examined the correlation between increasing concentrations of various factors (e.g., TGF-β, IL-6, or IL-10) and the presence of pulmonary hypertension [57][58][59][60][61]. Ultimately, despite the high prevalence and increased risk of mortality associated with pulmonary hypertension in patients with CKD, pulmonary hypertension remains insufficiently understood in patients with CKD [61].…”
Section: Pulmonary Hypertension In Patients With Ckdmentioning
confidence: 99%
“…PH patients, in particular group 3 due to hypoxia or lung disease, usually display low L-Arg levels compared to healthy subjects. 4 , 23 Consequently, increasing the substrate for NO production (L-Arg supplementation) is thought to attenuate PH development in both monocrotaline- 24 and hypoxia-challenged 25 rats. In PH patients, L-Arg supplementation considerably reduces pulmonary vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] More recently, investigators have derived additional risk assessment strategies, but molecular biomarkers are still lacking. 32,[35][36][37] Using LC-MS/MS, Sandqvist et al 21 identified significant upregulation of ADMA and symmetric dimethylarginine (SDMA) levels in the plasma of 21 PAH patients compared to 14 patients with left ventricular systolic dysfunction (LVSD) patients and 27 HCs. According to the results, L-arginine levels and the L-arginine/ADMA ratio were significantly lower in PAH patients than in HCs and were correlated with 6MWD (r = 0.58, p = 0.006) and the World Health Organization (WHO) functional class (r = −0.46, p = 0.043), respectively, in PAH patients.…”
Section: Prognostic/predictive Biomarkers For Pahmentioning
confidence: 99%